Efficacy of splenectomy in patients with non-hodgkin's lymphomas associated with autoimmune hemolytic anemia and Evans — Fisher syndrome - Yevstakhevych, Y.L.; Vyhovska, Y.I.; Yevstakhevych, I.Y.; Semerak, M.M.; Lebed, H.B.; Loginsky, V.E. (Онкологія, 2017)
Objective: to determine indications for surgical technique and outcomes of splenectomy in non-Hodgkin’s lymphomas (NHL) associated with autoimmune hemolytic anemia (AIHA) or Evans — Fisher syndrome (EFS) based on our 20-year experience. Subject and methods: ten splenectomies in NHL associated with AIHA (group I) and 18 splenectomies in NHL associated with AIHA and immune thrombocytopenia — EFS (group II) have been performed. Outcomes were determined both post-operatively and over a long-term follow up observation during 3–201 months (median 68 months) and 1–290 months (median 195.5 months) in group I and group II, respectively. Results: splenectomy in NHL is indicated in those immune cytopenias refractory to steroids and cytotoxic therapy associated with massive splenomegaly, regional portal hypertension and hypersplenism. The surgical technique of splenectomy in large spleen is quite complicated and depends on both the spleen size and presence of adhesions. Postoperative mortality (progression of lymphoma, bleeding) reaches 7%. A favorable immediate outcome of surgery was observed in 93% of patients. Median value of postoperative event-free survival in NHL with AIHA reached 29.0 months (12.0–49.0 months), and median value of overall survival estimated 31.0 months (18.1–52.2 months), with a 3-year survival observed in 45% of patients and a 5-year survival in 22% of patients. Median event-free survival in patients with NHL and EFS reached 22 months (5.0–52.0 months), while median overall survival being 50 months (12.0–97.0 months), with a 3-year survival observed in as much as 62% of patients and a 5-year survival in 31% of patients. The lowest post-spenectomy life expectancy was stated in patients with aggressive lymphomas associated with immune cytopenias (diffuse large B-cell lymphoma, T-cell types). Conclusions: splenectomy has proved both an effective and quite safe treatment option and diagnostic tool in NHL complicated by immune cytopenias, particularly those associated with massive splenomegaly, regional portal hypertension and hypersplenism. Long-term results of splenectomy are mainly determined by a variant of NHL.